Utility of combined solid and liquid biopsy for molecular profiling in lung adenocarcinoma: Insights from a real-world case - Bharat Bhosale; Gunj Bafna; Paridhy Vanniya Subramanyam; Kapil Salgia; Sadia Afreen; Jinumary John; Vyomesh Javle; Kritika Verma; N.R. Naavarasi; Sreekanth Reddy Peddagangannagari; Akhil Gorla; Giridharan Periyasamy; et al. (The Journal of Liquid Biopsy)
Lung adenocarcinoma is a subtype of NSCLC that is often associated with poor prognosis. We present a case of metastatic lung adenocarcinoma in which comprehensive genomic profiling using both solid and liquid biopsies was employed to monitor disease progression and guide targeted therapy decisions. An initial liquid biopsy detected ROS1-CCDC6 gene fusion, and the patient was started on Crizotinib. Following disease progression, further genomic profiling using both solid tissue and cfDNA revealed the presence of a previously undetected classical mutation EGFR exon 21, p. L858R. Consequently, the treatment was adjusted to include both Crizotinib and Gefitinib. A 6-month follow-up showed relapse and extensive metastasis. A repeat liquid biopsy identified a newly acquired TP53 mutation (exon 7, p.R248Q) in addition to the persistent EGFR mutation. Restarting the targeted therapy led to complete metabolic resolution of the disease. This case highlights the utility of liquid biopsy when tissue biopsy is not feasible and underscores the importance of integrating both solid and liquid genomic data to capture a more comprehensive mutational landscape, including low-frequency or emerging variants, ultimately enabling more effective, individualized treatment strategies.